PENGARUH PEMBIAYAAN PENDIDIKAN DAN KUALITAS PELAKSANAAN PEMBELAJARAN TERHADAP PRESTASI BELAJAR EKONOMI SISWA DI SMA NEGERI 2 JENEPONTO - Andi Mulyadi Radjab; Lahaya . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This study aims to know the influence of financing education and quality of learning implementation of the student’s economic learning outcomes in SMA Negeri 2 Jeneponto, Jeneponto regency, academic year 2017/2018. The population in this study were 395 students of majoring in social science and the sample was 59 students. The method used in this study is quantitative research with ex post facto approach. The first and second hypothesis test used simple linear regression analysis, the third hypothesis test used  multiplelinear regression. The result of the study showed that (1) the financing education seen from indirect costs and personal costs aspect the which has positive and significant impact on student’s economic learning outcomes which is was seen by the knowledge  and skills aspect. (2) the quality of student learning implementation is seen by the materials learning aspect, teaching and learning activities, methods, tools and learning sources whitch have positif and significant impact on student’s economic learning outcomes which is seen by the knowledge and skills. (3) the financing education and the quality of learning implementation simultan eously have positive and significant impact on the student’s economic learning outcomes which is seen by the knowledge and skills aspect of students of SMA Negeri 2 Jeneponto academic year 2017/2018. Keyword : Financing education, quality of learning implementation, student’s economic, learning outcomes.